Immunosuppressive effects of the standardized extract of Phyllanthus amarus on cellular immune responses in Wistar-Kyoto rats - Ilangkovan M; Jantan I; Mesaik MA; Bukhari SNA (Dove Medical Press, 2015)
Menaga Ilangkovan, Ibrahim Jantan, Mohamed Ahmed Mesaik, Syed Nasir Abbas BukhariDrug and Herbal Research Center, Faculty of Pharmacy, Universiti Kebangsaan Malaysia, Kuala Lumpur, MalaysiaAbstract: Phyllanthus amarus (family: Euphorbiaceae) is of immense interest due to its wide spectrum of biological activities. In the present study, the standardized 80% ethanol extract of P. amarus was investigated for its modulatory activity on various cellular immune parameters, including chemotaxis of neutrophils, engulfment of Escherichia coli by neutrophils, and Mac-1 expression, in leukocytes isolated from treated/nontreated Wistar-Kyoto rats. The detailed cell-mediated activity of P. amarus was also investigated, including analysis of the effects on T- and B-cell proliferation and CD4+ and CD8+ T-cell subsets in splenic mononuclear cells, and estimation of serum cytokine production by activated T-cells. The main components of the extract, phyllanthin, hypophyllanthin, corilagin, geraniin, ellagic acid, and gallic acid were identified and quantitatively analyzed in the extracts, using validated reversed-phase high-performance liquid chromatography (HPLC) methods. N-formyl-methionyl-leucyl-phenylalanine (fMLP)-induced neutrophils isolated from rats administered with the extract of P. amarus, at doses ranging from 100 to 400 mg/kg for 14 days, revealed a significant dose-dependent reduction in neutrophil migration (P<0.05). Similar patterns of inhibition were also observed in phagocytic activity and in fMLP-induced changes in expression of β2 integrin polymorphonuclear neutrophils. The results in P. amarus-treated rats also demonstrated a dose-dependent inhibition of both lipopolysaccharide-stimulated B-cell proliferation and concanavalin A–stimulated T-cell proliferation as compared with sensitized control. At a dose of 400 mg/kg (P<0.01), there was a significant decrease in the (%) expression of CD4+ and CD8+ in splenocytes and in serum cytokines of T helper (Th1) (IL-2 and IFN-γ) and Th2 (IL-4). In conclusion, P. amarus showed effective immunosuppressive activities in cellular immune response, by various immune regulatory mechanisms, and may be useful for improvement of immune-related disorders.Keywords: immunosuppression, leukocytes migration, phagocytic activity, splenic mononuclear cells, T- and B-cell proliferation